Comparative study of IPv4 and IPv6 and migration to IPv6 in mobile networks - Teo, Han Wei. (2008)
Recent development in mobile computing has increased the demand for mobile networking. Wireless LAN is one of the many mobile networks receiving tremendous attention in the recent years. Wireless LANs are extensions to wired networks that allow Mobile Nodes to be connected to the network via the Access Point. The Internet Protocol (IP) is used to enable nodes in different networks communicate with each other. End-to- end connectivity across heterogeneous networks is possible with Internet Protocol version 4 (IPv4). Certain limitations in IPv4 (e.g. depleting address space) has led to the development of Internet Protocol version 6 (IPv6). IPv6 provides much larger address space, mandatory security mechanism, support for mobility and QoS. To migrate to IPv6 in mobile networks, particularly in Wireless LANs, transition mechanisms have to be deployed to connect IPv6 islands, and to enable communications between IPv4 and IPv6 nodes. This project investigates the implementation of IPv4 in Wireless LANs, and its limitations. The implementation of IPv6, as well as migration to IPv6 in Wireless LANs is then studied. Different types of transition mechanism are investigated from the Wireless LAN’s perspective.